Corruption in Formal Adult Education in Nigeria: Implications for Sustainable National Development - Kevin Chinweikpe, WAMI, (MultiTech Publisher, 2024)
This position paper took a cursory view of corruption, examined adult education, assessed corruption in formal adult education and highlighted the implications for sustainable national development in Nigeria. The paper concluded that concerted efforts must be put in place in order to curb the menace of corruption in adult education. Adult education is the poorest sector in education in terms of allocation of financial resources. Government allocates meagre financial resources annually to adult education organizations, yet corrupt financial practices are perpetrated by the operators of adult education institutions in Nigeria. There is equally the challenge of cheating in examination and examination malpractice. These have stifled the developmental needs of the country to be provided by adult education. It was suggested that the EFCC and ICPC should beam their searchlight on adult education sector of education with a view to recovering stolen funds arresting and prosecuting offenders of embezzlement and misappropriation of education funds; adult learners found guilty of corrupt practices should have their admission revoked; adult educators found guilty of the monetary extortion should be relieved of their jobs; and government should make it as a point of duty to allocate 3% of her education budget to adult education annually.